Immunological considerations for laboratory staff and COVID-19 biosafety - Ambroise Kouame Kintossou; Stephanie Villar; Zisis Kozlakidis (Elsevier, 2023)
The vulnerability of healthcare and laboratory to potential infection by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus has thus far been analyzed through the lens of the acute phase of the pandemic, including remote-based work, as well as emergency settings that are different from routine healthcare operations. However, as lockdowns ease and activities return to an identifiable pre-pandemic routine, the safety considerations also require to shift accordingly. As laboratory workers are likely to continue being exposed to unidentified SARS-CoV-2 positive samples through routine blood collection and processing operations, coronavirus disease 2019 (COVID-19) might have to be re-considered as an occupational disease within this context. Additionally, as per many such occupational diseases, a surveillance system is implemented for the medium- and long-term. This manuscript presents the views on the possible surveillance scenarios for laboratory staff, viewed from an immunological and biosafety perspective.